Method for producing composite particles, composite particles, and all-solid-state battery
A coating liquid with controlled PO4 unit ratios forms a thin coating film on positive electrode active material particles, addressing the issue of thick films and high resistance in sulfide-based all-solid-state batteries by improving coverage and stability.
Patent Information
- Application Number
- JP2022025718
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-02-22
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-02-22
AI Technical Summary
Conventional coating liquids for positive electrode active material particles in sulfide-based all-solid-state batteries result in thick coating films, leading to increased battery resistance due to reduced coverage and direct contact between the positive electrode active material particles and the sulfide solid electrolyte.
A coating liquid with a specific composition of phosphoric acid compounds, satisfying certain ratios of PO4 units, is used to form a thin coating film with high coverage, reducing direct contact and improving battery performance.
The thin coating film achieves high coverage and reduces battery resistance, enhancing the stability of the sulfide solid electrolyte and overall battery performance.
Smart Images

Figure 0007619301000003 
Figure 0007619301000004 
Figure 0007619301000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a coating liquid, a method for producing composite particles, composite particles, and an all-solid-state battery. [Background technology]
[0002] International Publication No. 2017 / 094416 (Patent Document 1) discloses immersing a positive electrode active material in a coating formation liquid containing lithium metaphosphate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2017 / 094416 Summary of the Invention [Problem to be solved by the invention]
[0004] It has been proposed to form a coating film containing phosphorus (P) on the surface of positive electrode active material particles. Conventionally, for example, an aqueous solution of lithium metaphosphate has been used as the coating liquid.
[0005] The coating film can cover the surface of the positive electrode active material particles. For example, in a sulfide-based all-solid-state battery, it is expected that the higher the coverage, the less the deterioration of the sulfide solid electrolyte will be. This is thought to be because direct contact between the positive electrode active material particles and the sulfide solid electrolyte is reduced. However, when the coverage is increased using a conventional coating solution, the coating film tends to become thicker. The thicker the coating film, the greater the possibility of an increase in battery resistance.
[0006] An object of the present disclosure is to provide composite particles having a high coverage and a thin coating film. [Means for solving the problem]
[0007] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0008] 1. The coating liquid includes a solute and a solvent. The solute includes a phosphoric acid compound. The coating liquid satisfies the relationship of the following formula (1). {I0 / (I0+I1+I2)}≦0.7 (1) In the above formula (1), I0 is 31 In the P-NMR spectrum, the Q 0 The area of the signal derived from the unit is shown. I1 is 31 In the P-NMR spectrum, the Q 1 The area of the signal derived from the unit is shown. I2 is 31 In the P-NMR spectrum, the Q 2 The area of the signal derived from the unit is shown.
[0009] In the coating solution, the phosphate compound may take various forms. That is, the coating solution may contain various PO4 units. For example, the coating solution may contain Q 0 Unit, Q 1 Units and Q 2 The ratio of these units can determine the solute composition. 0 Unit, Q 1 Units and Q 2 The units are represented by the following formulas (1-0) to (1-2).
[0010] [ka]
[0011] Q 0 The unit has the structure of the above formula (1-0). 0 The unit has no bonds. Q 0 The units are believed to be derived from liberated PO4 units (orthophosphate).
[0012] Q 1 The unit has the structure of the above formula (1-1). 1 The unit has one bond. Q 1 The units may, for example, be derived from a dimer of PO4 (P2O7).
[0013] Q 2 The unit has the structure of the above formula (1-2). 2 The unit has two bonds. Q 2 The units are believed to be derived, for example, from a chain structure (chain condensed phosphate).
[0014] The above formulas (1-0) to (1-2) are merely representative examples of each unit. Each unit may include various modifications. For example, in each formula, "-OH" dissociates to become "-O - For example, H may be substituted with another element. For example, it may be in the form of "-OLi", "-ONa", etc.
[0015] Hereinafter, the left side of the above formula (1) is "Q 0 Also written as "unit ratio". Q 0 It is believed that the smaller the unit ratio, the greater the proportion of phosphate compounds with long molecular chains.
[0016] Conventional coating liquid is Q 0 The unit ratio tends to be large. In other words, conventional coating solutions have a high Q 0 The unit ratio exceeds 0.7.
[0017] According to the new findings of this disclosure, Q 0 When the unit ratio is reduced to 0.7 or less, the coverage rate is improved and a thin coating film can be formed. It is believed that the large abundance ratio of the phosphoric acid compound with a long molecular chain makes it easier to generate a coating film with continuity. As a result, it is believed that the coverage rate is improved and a thin coating film can be formed.
[0018] 2. The coating liquid may further satisfy, for example, the relationship of the following formula (2). 0.17≦{I2 / (I0+I1+I2)} (2)
[0019] By further satisfying the relationship of the above formula (2), an improvement in the coverage is expected.
[0020] 3. The coating liquid may further satisfy, for example, the relationship of the following formula (3). I0 <I2(3)
[0021] By further satisfying the relationship of the above formula (3), an improvement in the coverage is expected.
[0022] 4. The coating liquid may further satisfy, for example, the relationship of the following formula (4). 0≦C Li / C P <1.1 (4) In the above formula (4), C Li C denotes the molar concentration of lithium in the coating solution. P indicates the molar concentration of phosphorus in the coating solution.
[0023] C Li / C P indicates the molar ratio (ratio of amounts of substance) of lithium (Li) and P. A molar ratio of less than 1.1 is expected to reduce precipitation.
[0024] 5. The solvent may include, for example, water.
[0025] 6. The solute may include, for example, at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid.
[0026] Metaphosphoric acid and polyphosphoric acid dissolve in the solvent, 0 The unit ratio tends to be smaller.
[0027] 7. The solute may further include, for example, sodium.
[0028] Phosphate compounds having long molecular chains may be decomposed into smaller molecules, for example, by solvolysis. According to the new findings of the present disclosure, the stability of phosphate compounds having long molecular chains may be improved by dissolving sodium (Na) in the coating solution.
[0029] 8. A method for producing composite particles includes the following (a) and (b): (a) A mixture is prepared by mixing a coating liquid with positive electrode active material particles. (b) drying the mixture to produce composite particles. The composite particles include positive electrode active material particles and a coating film. The coating film covers at least a part of the surface of the positive electrode active material particles. The coating film contains phosphorus.
[0030] The composite particles may be called "coated positive electrode active material". The coating liquid attached to the surface of the positive electrode active material particles dries to form a coating film. By using the coating liquid of "1 to 7." above, it is expected that a thin coating film will be formed and the coverage rate will be improved.
[0031] 9. (b) above may include forming composite particles, for example by spray drying.
[0032] 10. The composite particle includes a positive electrode active material particle and a coating film. The coating film covers at least a part of the surface of the positive electrode active material particle. The coating film contains phosphorus. The coating film has a thickness of 28.5 nm or less. The coverage rate measured by X-ray photoelectron spectroscopy is 83% or more.
[0033] The coverage can be measured by X-ray photoelectron spectroscopy (XPS). With a coverage of 83% or more, for example, in a sulfide-based all-solid-state battery, it is expected that deterioration of the sulfide solid electrolyte will be reduced. With a coating film thickness of 28.5 nm or less, it is expected that the battery resistance will be reduced. Hereinafter, the "coating film thickness" may be abbreviated to "film thickness".
[0034] 11. The all-solid-state battery includes a positive electrode layer, a separator layer, and a negative electrode layer. The separator layer is disposed between the positive electrode layer and the negative electrode layer. The positive electrode layer includes composite particles and a sulfide solid electrolyte.
[0035] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure. [Brief description of the drawings]
[0036] [Figure 1] FIG. 1 is an example of a 31P-NMR spectrum. [Diagram 2] FIG. 2 is a schematic flow chart of the method for producing composite particles in this embodiment. [Diagram 3] FIG. 3 is a conceptual diagram showing a composite particle in this embodiment. [Figure 4] FIG. 4 is a conceptual diagram showing the all-solid-state battery in this embodiment. [Diagram 5] FIG. 5 is a graph showing the relationship between the Q0 unit ratio and the coverage rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] <Definitions of terms, etc.> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0038] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0039] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only "one particle" but also "an aggregate of particles (powder, powder, particle group)."
[0040] Unless otherwise specified, the order of execution of the steps, operations, and the like included in various methods is not limited to the order described. For example, the steps may proceed simultaneously. For example, the steps may be performed in sequence.
[0041] For example, a numerical range such as "m to n%" includes the upper limit and the lower limit unless otherwise specified. That is, "m to n%" indicates a numerical range of "m% or more and n% or less". Furthermore, "m% or more and n% or less" includes "more than m% and less than n%". Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0042] All numerical values are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximations that may vary depending on the application of the disclosed technology. All numerical values may be expressed with significant figures. Measurements may be average values of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.
[0043] Geometric terms (e.g., "parallel," "perpendicular," "orthogonal," etc.) should not be interpreted in a strict sense. For example, "parallel" may deviate slightly from the strict meaning of "parallel." Geometric terms may include, for example, tolerances, errors, etc. in design, work, manufacturing, etc. The dimensional relationships in each drawing may not match the actual dimensional relationships. In order to facilitate understanding of the disclosed technology, the dimensional relationships (length, width, thickness, etc.) in each drawing may be changed. Furthermore, some configurations may be omitted.
[0044] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may also be allowed.
[0045] "D50" refers to the particle size at which the cumulative frequency from the smaller particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method.
[0046] " 31 P-NMR measurement》 " 31 P-NMR" stands for phosphorus-31 nuclear magnetic resonance (31 P Nuclear Magnetic Resonance) of the coating liquid. 31 The P-NMR spectrum can be measured by the following procedure. An FT-NMR instrument is prepared. For example, an FT-NMR instrument manufactured by JEOL Ltd., "Product name JNM-ECA 600II type" (or an equivalent product) may be used. A micro-bottom tube having a diameter of 5 mm is filled with a coating liquid (sample). The micro-bottom tube is set in the FT-NMR instrument. The measurement conditions are as follows:
[0047] Measurement temperature: room temperature (20±5℃) Pulse width: 30°, 4.0μs Repeat conditions: ACQTM = 0.56197s, PD = 30s Pulse mode: 31Pbcm Chemical shift reference: orthophosphoric acid (0 ppm) Observation frequency: 242.95MHz Observation width: 120 ppm (center observation value: 10 ppm) Sample rotation speed: 15Hz
[0048] Figure 1 shows 31 This is an example of a P-NMR spectrum. PO4 Q 0 The signal derived from the unit appears at a chemical shift near 0 ppm. The area (integral value) of the signal is regarded as "I0" in the above formula (1). PO4 Q 1 A signal derived from the unit appears at a chemical shift of about -10 to -13 ppm. The area of the signal is regarded as "I1" in the above formula (1). PO4 Q 2 A signal derived from the unit appears at a chemical shift of about -20 to -25 ppm. The area of the signal is regarded as "I2" in the above formula (1).
[0049] 《ICP measurement》 The mass concentrations of Li, P, and Na in the coating liquid can be measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES). The measurement procedure is as follows: 100 ml of sample liquid is prepared by diluting 0.01 g of the coating liquid with pure water. Aqueous solutions of Li, P, and Na (1000 ppm, 10000 ppm) are prepared. A standard solution is prepared by diluting 0.01 g of the aqueous solution with pure water. An ICP-AES device is prepared. For example, an ICP-AES device manufactured by Shimadzu Corporation (product name ICPE-9800) (or an equivalent product) may be used. The emission intensity of the standard solution is measured by the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The emission intensity of the sample solution (diluted solution of the coating liquid) is measured by the ICP-AES device. The mass concentrations of Li, P, and Na in the coating solution are determined from the emission intensity of the sample solution and the calibration curve. The mass concentrations of Li and P are then converted to molar concentrations. The molar concentration of Li (C Li ) is the molar concentration of P (C P ) to obtain the molar ratio (C Li / C P ) is obtained.
[0050] <XPS Measurement> The coverage of the composite particles can be measured by XPS. The measurement procedure is as follows: An XPS device is prepared. For example, an XPS device manufactured by ULVAC-PHI, Inc., product name: PHI X-tool (or equivalent) may be used. A sample powder consisting of composite particles is set in the XPS device. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. For example, an analysis software manufactured by ULVAC-PHI, Inc., product name: MulTiPak (or equivalent) may be used. The ratio of each element is obtained from the intensity values of the peaks of C1s, O1s, P2p, Mn2p3, Co2P3, and Ni2P3. The coverage rate is calculated by the following formula (5). θ=P / (P+Ni+Co+Mn)×100 (5) In the above formula (5), θ represents the coverage (%), and P, Ni, Co, and Mn represent the ratios of each element. Here, as an example, a measurement method in which the positive electrode active material particles are Li(NiCoMn)O2 is shown. The right side of the above formula (5) is changed according to the composition of the positive electrode active material particles. For example, when the positive electrode active material particles are LiNiO2, the right side of the above formula (5) is changed to "P / (P+Ni)×100".
[0051] <Film thickness measurement> The film thickness (thickness of the coating film) can be measured by the following procedure. A sample is prepared by embedding composite particles in a resin material. A cross-section is processed on the sample by an ion milling device. For example, an ion milling device "Product name Arblade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross-section of the sample is observed by an SEM (Scanning Electron Microscope). For example, an SEM device "Product name SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The film thickness is measured in 20 fields of view for each of 10 composite particles. The arithmetic average of the film thicknesses at a total of 200 points is regarded as the film thickness.
[0052] <Coating liquid> The coating liquid is used to form a coating film on the surface of the positive electrode active material particles. The coating liquid contains a solute and a solvent. The coating liquid may further contain, for example, a suspended matter (undissolved component), a precipitate, etc.
[0053] 《Solute》 The amount of the solute may be, for example, 0.1 to 20 parts by mass, 1 to 15 parts by mass, or 5 to 10 parts by mass relative to 100 parts by mass of the solvent. By dissolving the solute in the solvent, various PO4 units can be produced.
[0054] Q 0 Unit Comparison Q 0 The unit ratio is calculated by "I0 / (I0+I1+I2)" [see formula (1) above]. The coating liquid has a Q of 0.7 or less. 0 This is expected to result in a high coverage and a thin coating film. 0 The smaller the unit ratio, the higher the coverage is expected. 0 The unit ratio may be, for example, 0.57 or less, 0.39 or less, 0.15 or less, 0.14 or less, or 0.09 or less. 0 The unit ratio may be, for example, zero or may be 0.09 or more. 0 The unit ratio may be, for example, 0.09 to 0.57.
[0055] Q 1 Unit Comparison Q 1 The unit ratio is calculated by "I1 / (I0+I1+I2)". The coating liquid has a Q of, for example, more than 0.05. 1 It may have a unit ratio. 1 The unit ratio may be, for example, 0.10 or more, 0.20 or more, or 0.40 or more. 1 The unit ratio may be, for example, 0.70 or less, 0.60 or less, or 0.5 or less. 1 The unit ratio may be, for example, 0.40 to 0.47.
[0056] Q 2 Unit Comparison Q 2 The unit ratio is calculated by "I2 / (I0+I1+I2)". The coating liquid has a Q value of, for example, more than 0.01. 2 It may have a unit ratio. 2 The higher the unit ratio, the higher the coverage rate is expected. 2The unit ratio may be, for example, 0.03 or more, 0.17 or more, 0.39 or more, or 0.45 or more (see formula (2) above). 2 The unit ratio may be, for example, 0.03 to 0.45.
[0057] Q 2 Unit ratio is Q 0 It may be larger than the unit ratio (see formula (3) above). Q 0 Q to unit ratio 2 The unit ratio (I2 / I0) may be, for example, 2 or more, 2.6 or more, or 5 or more. The ratio (I2 / I0) may be, for example, 5 or less. The ratio (I2 / I0) may be, for example, 1 to 5.
[0058] Q 1 Unit Ratio and Q 2 The sum of the unit ratio [(I1+I2) / (I0+I1+I2)] may be, for example, 0.40 or more, 0.43 or more, 0.50 or more, 0.62 or more, 0.85 or more, or 0.91 or more. 1 Unit Ratio and Q 2 The sum of the unit ratio may be, for example, 1.00, or may be 0.91 or less. 1 Unit Ratio and Q 2 The sum of the unit ratio may be, for example, 0.43 to 0.91. 1 Unit Ratio and Q 2 The sum with the unit ratio is, for example, Q 0 It may be larger than the unit ratio.
[0059] Phosphate compounds The solute contains a phosphoric acid compound. 0The solute may contain any phosphoric acid compound as long as the unit ratio is 0.7 or less. The solute may contain, for example, at least one selected from the group consisting of orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid, and polyphosphoric acid. The solute may contain, for example, at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid. When metaphosphoric acid or polyphosphoric acid is dissolved in a solvent, Q 0 The unit ratio tends to be smaller.
[0060] Lithium compounds The solute may further include a lithium compound. The solute may include, for example, lithium hydroxide, lithium carbonate, lithium nitrate, etc. The molar ratio of Li to P (C Li / C P ) may be, for example, less than 1.1 (see formula (4) above). Li / C P It is expected that a molar ratio (C) of less than 1.1 will reduce precipitation. Li / C P ) may be, for example, 1.07 or less, 0.45 or less, or zero. Li / C P ) may be, for example, 0 to 0.45 or 0.45 to 1.07.
[0061] "sodium" The solute may further contain Na. When Na is dissolved in the coating liquid, the stability of the phosphate compound having a long molecular chain may be improved. The concentration (mass concentration) of Na in the coating liquid may be, for example, 0 to 1%. The concentration of Na may be, for example, 0.6% or less, or 0.5% or less. The concentration of Na may be, for example, 0.5 to 0.6%.
[0062] "solvent" The solvent may contain any component as long as the solute dissolves in the solvent. The solvent may contain, for example, water, alcohol, etc. The solvent may contain, for example, ion-exchanged water, etc.
[0063] <Method of manufacturing composite particles> 2 is a schematic flow chart of the method for producing composite particles in this embodiment. Hereinafter, "the method for producing composite particles in this embodiment" may be abbreviated as "the present production method". The present production method includes "(a) preparation of a mixture" and "(b) production of composite particles". The present production method may further include, for example, "(c) heat treatment" or the like.
[0064] (a) Preparation of the mixture The present manufacturing method includes preparing a mixture by mixing a coating liquid with positive electrode active material particles. The mixture may be, for example, a suspension or a wet powder. For example, a suspension may be formed by dispersing positive electrode active material particles (powder) in a coating liquid. For example, a wet powder may be formed by spraying a coating liquid into a powder. In the present manufacturing method, any mixing device, granulating device, etc. may be used.
[0065] The positive electrode active material particles may be secondary particles (aggregates of primary particles). The positive electrode active material particles (secondary particles) may have a D50 of, for example, 1 to 50 μm, may have a D50 of 1 to 20 μm, or may have a D50 of 5 to 15 μm.
[0066] One type of positive electrode active material particle may be used alone, or two or more types of positive electrode active material particles may be used in combination. The positive electrode active material particles may contain at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, and LiFePO4. For example, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the sum of the composition ratios in parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. Li(NiCoMn)O2 is, for example, Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2, Li(Ni 0.5 Co 0.2 Mn0.3 )O2, Li(Ni 0.8 Co 0.1 Mn 0.1 ) O2, etc.
[0067] (b) Production of Composite Particles The present manufacturing method includes producing composite particles by drying the mixture. The coating liquid attached to the surface of the positive electrode active material particles is dried to produce a coating film. In the present manufacturing method, any drying method can be used.
[0068] For example, the composite particles may be formed by a spray-drying method. That is, the suspension is sprayed from a nozzle to form droplets. The droplets contain the positive electrode active material particles and the coating liquid. For example, the droplets are dried by hot air to form the composite particles. The use of the spray-drying method is expected to improve, for example, the coverage rate.
[0069] The solid content of the suspension for spray drying may be, for example, 1 to 50% or 10 to 30% by volume. The nozzle diameter may be, for example, 0.1 to 10 mm or 0.1 to 1 mm. The hot air temperature may be, for example, 100 to 200°C.
[0070] For example, the composite particles may be produced by a tumbling fluidized bed coating apparatus. In the tumbling fluidized bed coating apparatus, "(a) preparation of the mixture" and "(b) production of the composite particles" can be carried out simultaneously.
[0071] (c) Heat Treatment The present manufacturing method may include subjecting the composite particles to a heat treatment. The coating film may be fixed by the heat treatment. The heat treatment here may also be called "baking". In the present manufacturing method, any heat treatment device may be used. The heat treatment temperature may be, for example, 150 to 300°C. The heat treatment time may be, for example, 1 to 10 hours. For example, the heat treatment may be performed in air or in an inert atmosphere.
[0072] <Composite particles> 3 is a conceptual diagram showing a composite particle in this embodiment. The composite particle 5 includes a positive electrode active material particle 1 and a coating film 2. The composite particle 5 may form an aggregate, for example. That is, one composite particle 5 may include two or more positive electrode active material particles 1. The positive electrode active material particle 1 is the core of the composite particle 5. The details of the positive electrode active material particle 1 are as described above.
[0073] The coating film 2 is a shell of the composite particle 5. The coating film 2 covers at least a part of the surface of the positive electrode active material particle 1. The composite particle 5 has a coverage of 83% or more. It is expected that the higher the coverage, the more the deterioration of the sulfide solid electrolyte in the all-solid-state battery is reduced. The coverage may be, for example, 85% or more, 88% or more, 91% or more, or 92% or more. The coverage may be, for example, 100% or less, 99% or less, or 95% or less. The coverage may be, for example, 83 to 92%.
[0074] The coating film 2 has a thickness of 28.5 nm or less. The thinner the film thickness, the more the battery resistance is expected to be reduced. The coating film 2 may have a thickness of, for example, 26.9 nm or less, 26.8 nm or less, 26.2 nm or less, or 25.4 nm or less. The coating film 2 may have a thickness of, for example, 10 nm or more, 20 nm or more, or 25.4 nm or more. The coating film 2 may have a thickness of, for example, 25.4 to 28.5 nm.
[0075] The coating film 2 contains a phosphorus compound. That is, the coating film 2 contains P. The coating film 2 may further contain Li. The coating film 2 may further contain, for example, oxygen (O), carbon (C), etc.
[0076] <All-solid-state battery> FIG. 4 is a conceptual diagram showing an all-solid-state battery in this embodiment. The all-solid-state battery 100 may include, for example, an exterior body (not shown). The exterior body may be, for example, a pouch made of an aluminum laminate film. The exterior body may house a power generating element 50. The power generating element 50 includes a positive electrode layer 10, a separator layer 30, and a negative electrode layer 20. That is, the all-solid-state battery 100 includes a positive electrode layer 10, a separator layer 30, and a negative electrode layer 20. The all-solid-state battery 100 may further include, for example, a positive electrode collector, a positive electrode tab, a negative electrode collector, a negative electrode tab, etc. (none of which are shown).
[0077] Positive electrode layer The positive electrode layer 10 includes composite particles and a sulfide solid electrolyte. The details of the composite particles are as described above. The sulfide solid electrolyte can form an ion conduction path in the positive electrode layer 10. The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, with respect to 100 parts by volume of the composite particles (positive electrode active material). The sulfide solid electrolyte includes, for example, Li, P, and sulfur (S). The sulfide solid electrolyte may further include, for example, O, silicon (Si), or the like. The sulfide solid electrolyte may further include, for example, a halogen, or the like. The sulfide solid electrolyte may further include, for example, iodine (I), bromine (Br), or the like. The sulfide solid electrolyte may be, for example, glass ceramics or argyrodite. The sulfide solid electrolyte may include, for example, at least one selected from the group consisting of LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, and Li3PS4.
[0078] The positive electrode layer 10 may further include, for example, a conductive material. The conductive material can form an electronic conduction path in the positive electrode layer 10. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The conductive material may include any component. The conductive material may include, for example, at least one selected from the group consisting of carbon black, vapor grown carbon fiber (VGCF), carbon nanotubes (CNT), and graphene flakes.
[0079] The positive electrode layer 10 may further include, for example, a binder. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The binder may include any component. The binder may include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), styrene butadiene rubber (SBR), and polytetrafluoroethylene (PTFE).
[0080] Negative electrode layer The negative electrode layer 20 is a counter electrode of the positive electrode layer 10. The negative electrode layer 20 includes negative electrode active material particles and a sulfide solid electrolyte. The negative electrode layer 20 and the positive electrode layer 10 may share the same sulfide solid electrolyte or may be different sulfide solid electrolytes. The negative electrode layer 20 may further include a conductive material and a binder. The negative electrode active material particles may include any component. The negative electrode active material particles may include, for example, graphite, Si, silicon oxide [SiO x (0 <x<2)〕、およびLi4Ti5O 12 may contain at least one selected from the group consisting of:
[0081] <Separator layer> The separator layer 30 is interposed between the positive electrode layer 10 and the negative electrode layer 20. The separator layer 30 separates the positive electrode layer 10 from the negative electrode layer 20. The separator layer 30 includes a sulfide solid electrolyte. The separator layer 30 may further include a binder. The sulfide solid electrolyte may be common to the separator layer 30 and the positive electrode layer 10, or may be different. The sulfide solid electrolyte may be common to the separator layer 30 and the negative electrode layer 20, or may be different. EXAMPLES
[0082] <Production of composite particles> Composite particles No. 1 to 8 were produced as follows. Hereinafter, for example, "composite particle No. 1" may be abbreviated as "No. 1."
[0083] No.1 A coating solution was prepared by dissolving 10.8 parts by mass of orthophosphoric acid (85%, Kishida Chemical Co., Ltd.) in 166 parts by mass of ion-exchanged water. Furthermore, 2.1 parts by mass of lithium hydroxide monohydrate (LiOH·H2O) was further dissolved in the coating solution. 0 Unit ratio [I0 / (I0+I1+I2)], molar ratio (C Li / C P The concentrations of Na, Na, and Na were measured. The results are shown in Table 1 below.
[0084] As the positive electrode active material particles, Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 )O2 was prepared. A suspension was prepared by dispersing a powder of positive electrode active material particles in a coating liquid. A spray dryer manufactured by BUCHI (product name: Mini Spray Dryer B-290) was prepared. A powder of composite particles was produced by supplying the suspension to the spray dryer. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 The composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours.
[0085] The coverage and film thickness were measured using the procedures described above, and the results are shown in Table 1 below.
[0086] A positive electrode layer including the composite particles and the sulfide solid electrolyte was formed. A test battery including the positive electrode layer was further manufactured. The test battery was an all-solid-state battery. The initial resistance of the test battery was measured. The results are shown in Table 1 below. The initial resistance values in Table 1 below are relative values. The initial resistance of No. 4 is defined as 1.
[0087] No.2 A coating solution was prepared by dissolving 2.7 parts by mass of lithium metaphosphate (manufactured by Mitsuwa Chemical Co., Ltd.) in 50 parts by mass of ion-exchanged water. Except for this, composite particles and test batteries were manufactured in the same manner as in No. 1.
[0088] No.3 The coating solution of No. 1 was mixed with positive electrode active material particles to prepare a suspension. The suspension was fed to a spray dryer to produce composite particles. In No. 3, the coating conditions (mixing ratio of the coating solution to the positive electrode active material particles) were changed to increase the coverage. Furthermore, a test battery was produced in the same manner as No. 1.
[0089] No.4 A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. 2.1 parts by mass of lithium hydroxide monohydrate was further dissolved in the coating solution. Then, composite particles and test batteries were manufactured in the same manner as in No. 1.
[0090] No.5 Composite particles and test cells were prepared similarly to No. 4, except that no lithium hydroxide monohydrate was added to the coating solution.
[0091] No.6 The amount of lithium hydroxide monohydrate added to the coating solution was changed to change the molar ratio (C Li / C P Composite particles and test cells were prepared similarly to No. 4, except that the 100% 15 ...
[0092] No.7 The amount of lithium hydroxide monohydrate added to the coating solution was changed to change the molar ratio (C Li / C P Composite particles and test cells were prepared similarly to No. 4, except that the 100% 15 ...
[0093] No.8 A coating solution was prepared by dissolving 10 parts by mass of polyphosphoric acid (product name: Polyphosphoric acid-116T, manufactured by Nippon Chemical Industry Co., Ltd.) in 166 parts by mass of ion-exchanged water. Except for this, composite particles and test batteries were manufactured in the same manner as in No. 4.
[0094] [Table 1]
[0095] <Result> Figure 5 shows the Q 0 1 is a graph showing the relationship between unit ratio and coverage rate. 0 A high coverage rate is obtained in the area where the unit ratio is 0.7 or less. 0 The smaller the unit ratio, the higher the coverage rate tends to be. 0 In the region where the unit ratio is 0.7 or less, there is a tendency for the initial resistance to be small (see Nos. 4 to 8 in Table 1 above).
[0096] Q 0 In the region where the unit ratio exceeds 0.7, the coverage rate tends to be low and the initial resistance tends to be large (see No. 1 and 2 in Table 1 above). This is thought to be because the positive electrode active material particles come into direct contact with the sulfide solid electrolyte, causing the sulfide solid electrolyte to deteriorate.
[0097] Q0 Even if the unit ratio exceeds 0.7, the coverage can be increased by, for example, adjusting the coating conditions (see No. 3 in Table 1 above). However, 0 When the unit ratio exceeds 0.7, the film thickness increases as the coverage increases. There is a tendency for the initial resistance to increase significantly with an increase in film thickness.
[0098] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]
[0099] 1 positive electrode active material particle, 2 coating film, 5 composite particle, 10 positive electrode layer, 20 negative electrode layer, 30 separator layer, 50 power generating element, 100 all-solid-state battery.
Claims
1. (a) preparing a mixture by mixing a coating liquid with positive electrode active material particles; and (b) drying the mixture to produce composite particles; Including, The composite particles include the positive electrode active material particles and a coating film, the coating film covers at least a part of the surface of the positive electrode active material particle, The coating film contains phosphorus, The coating liquid includes a solute and a solvent, The solute includes at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid, The following formula (1): {I 0 / (I 0 +I 1 +I 2 )}≦0.7 (1) Fulfilling the relationship, In the above formula (1), I 0 teeth, 31 In the P-NMR spectrum, PO 4 Q 0 indicates the area of the signal derived from the unit, I 1 teeth, 31 In the P-NMR spectrum, PO 4 Q 1 indicates the area of the signal derived from the unit, I 2 teeth, 31 In the P-NMR spectrum, PO 4 Q 2 The area of the signal derived from the unit is shown. A method for producing composite particles.
2. The following formula (2): 0.17≦{I 2 / (I 0 +I 1 +I 2 )} (2) Further satisfying the relationship of The method for producing the composite particle according to claim 1 .
3. The following formula (3): I 0 <I 2 (3) Further satisfying the relationship of The method for producing the composite particle according to claim 1 or 2.
4. The following formula (4): 0≦C Li / C P <1.1 (4) Further satisfying the relationship In the above formula (4), C Li represents the molar concentration of lithium in the coating solution, C P represents the molar concentration of phosphorus in the coating liquid; The method for producing the composite particle according to any one of claims 1 to 3.
5. The solvent comprises water. The method for producing the composite particle according to any one of claims 1 to 4.
6. The solute further comprises sodium. The method for producing the composite particle according to any one of claims 1 to 5.
7. (b) includes forming the composite particles by a spray drying method; The method for producing the composite particle according to claim 1 .
8. Positive electrode active material particles; A coating film; Including, the coating film covers at least a part of the surface of the positive electrode active material particle, The coating film contains phosphorus, The coating film has a thickness of 28.5 nm or less, The coverage as measured by X-ray photoelectron spectroscopy is 83% or more. composite particles.
9. A positive electrode layer; A separator layer; A negative electrode layer; Including, the separator layer is disposed between the positive electrode layer and the negative electrode layer; The positive electrode layer includes the composite particle according to claim 8 and a sulfide solid electrolyte. All-solid-state battery.
Citation Information
Patent Citations
Galvanized steel sheet excellent in adhesive property, workability and weldability, and its production method
JP2002053974A
Coating composition, method of forming film having optical catalytic function, and optical catalytic member
JP2005171029A
Positive electrode active material for lithium secondary batteries, positive electrode for lithium secondary batteries, lithium secondary battery, method for producing positive electrode active material for lithium secondary batteries, and method for manufacturing lithium secondary battery
WO2017094416A1